A global perspective on women in leadership and work-family integration : breaking balance - Weber, Margaret J.; Cissna-Heath, Kerri (Cambridge Scholars Publishing, 2020)
There are countless books on the market that address the personal challenges and institutional barriers that ambitious female leaders face in the United States. This volume furthers the conversation by comparing the experiences of women in leadership with regards to work-life balance from eight different countries around the globe. Collecting stories from women in the United States, Costa Rica, India, Iran, Nigeria, Norway, Sri Lanka, and Uganda, this volume provides insights into the issues women face globally regarding leadership and work-family integration. It offers a variety of perspectiv.